Types of Institutions and Well-Being of Self-Employed and Paid Employees in Europe - Michael Fritsch; Alina Sorgner; Michael Wyrwich (Institute of Labor Economics (IZA), 2019)
This paper analyzes the role of different types of institutions, such as entrepreneurship-facilitating entry conditions, labor market regulations, quality of government, and perception of corruption for individual well-being among self-employed and paid employed individuals. Well-being is operationalized by job and life satisfaction of individuals in 32 European countries measured by data from EU Statistics on Income and Living Conditions (EU-SILC). We find that institutions never affected both occupational groups in opposite ways. Our findings indicate that labor market institutions do not play an important role well-being. The results suggest that fostering an entrepreneurial society in Europe is a welfare enhancing strategy that benefits both, the self-employed and paid employees.
Keywords: L26; I31; D01; D91; P51; 330; entrepreneurship; institutions; well-being; life satisfaction; job satisfaction